Adaptivt styrsystem för applicering på extraljus till fordon - Nyberg, Andreas; Wallin, Oliver (My University, 2019)
When analyzing the safety issues in traffic, one of the major concerns is the visibility. The driver needs a good view of the road surface and the nearby area to be able to see hazards such as poor roadway, wild animals that is walking onto the road or people who are in a vulnerable situation. At present time, if you do not have enough good view of the road the first solution is to use auxiliary lights that you place on the car to get a larger field of view in the dark. But the use of auxiliary lights is far from optimal, and an unnecessarily large area is illuminated, which risks disturbing both nearby citizens and, to a greater extent, dazzling fellow road users. In order to maintain good visibility without having large auxiliary lights, smart auxiliary lights can be implemented instead, by using smaller auxiliary lights with a focused light beam which is automatically angled towards the desired area, the good visibility can be achieved without having to illuminate unnecessarily large areas. The underlying dynamics between the vehicle's driving performance and the desired light focus area are analyzed and used to develop a useful prototype. The mechanical prototype is developed and optimized to cope with stresses such as the air flow and such during travel. The underlying control system is developed to give the driver a useful light image in front of the car when traveling in different conditions and road types. The system uses the CAN bus and a gyroscope to read and calculate out how the car is moving on the road. The prototype turns out to work well during testing and follows the road both vertically and sideways. Some optimization is required to increase the accuracy as it requires a certain database to be able to predict the road in front of the cars appearance.
Keywords: Auxiliary lights; traffic safety; CAN-bus